Promoting menstrual health and hygiene—insights from the 2023 World Menstrual Hygiene Day celebration events in the Hohoe municipality in Ghana - Sitsofe Gbogbo; Israel Wuresah; Phyllis Addo; Senam Klomegah; Emmanuel Gbogbo; Wisdom Axame; Priscilla Klutse; Christopher Makam; Robert Kokou Dowou; Paramount Eli Nelson; Ishmael Boateng; Sarah Odi Mantey; et al. (Frontiers in Public Health, 2024)
The 2023 World Menstrual Hygiene Day (WMHD) celebration at the University of Health and Allied Sciences (UHAS) sought to create awareness about menstruation. Toward normalizing menstruation, the 3-day event brought together key stakeholders and engaged community members on various topics relating to menstruation. Among the stakeholders were basic school teachers (13), school children (155), in a 2:1 female vs. male ratio within the ages of 10–17 years, School Health and Education Program Coordinators (2), Health Officers (4), Academicians (15), University students (35), Media representatives (3), and Civil society representatives (130). Particular among these discussions were the biology of menstruation, nutrition related facts during menstruation, sociocultural, and mental health issues surrounding menstruation. These discussions were intended to incite more conversations about menstruation, and contribute toward the agenda 2030 goal of making menstruation a normal fact of life. The paper describes activities conducted to improve menstrual health, reduce period poverty, and involve men in breaking the stigma around menstruation. This contributes to creating supportive environments for menstruating individuals. Meanwhile, the lessons from the activities to celebrate WMHD in Ghana are relevant for other communities to consider replicating with consideration for contextual differences.